Calculation of low bandgap homopolymers: Comparison of TD-DFT methods with experimental oligomer series - Oliveira, Eliezer Fernando [UNESP]; Roldao, Juan Carlos [UNESP]; Milián-Medina, Begoña; Lavarda, Francisco Carlos [UNESP]; Gierschner, Johannes (Elsevier, 2016)
The performance of different DFT functionals (B3LYP, BHLYP, CAM-B3LYP, M06HF) on the prediction of vertical transition energies Evert of low bandgap homopolymers is tested against the experimentally available oligomer series (thienopyrazines and thienothiophenes). This allows for a detailed and accurate comparison on the consistency of DFT methods for chainlength evolution and polymer limit prediction, and for an understanding of geometry and time-dependent contributions to Evert by combinatorial analysis. Together with former studies on wide/medium bandgap polymers and low bandgap co-polymers, our results on low bandgap homopolymers suggest offset-corrected M06HF as the most viable method for time inexpensive and reliable prediction of semiconducting polymers at the moment.